Aquatic science colloquium 2012 (AQUAColl 2012) : experience sharing in Aquatic Science Reseach II, Talang-Satang National Park To Santubong - Nyanti, L.; Norhadi, I.; Samsur, M; Ruhana, Hassan; Rahim, S.A.K.A (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The Sibu Laut River is located at the western boundary of the Kuching Wetland National Park and therefore it is important that the water quality be preserved for the health of aquatic life. A study was conducted in August 2011 to determine the water quality at five selected stations during high tide and low tide. Results of the study showed that temperature ranged from 29.0 - 30.8 °C. Salinity ranged from 28.3 - 33.3 PSU and 23.0 - 31.3 PSU during high tide and low tide, respectively. During high tide, salinity was generally higher than low tide and salinity at the bottom was higher than the surface. During low tide, transparency was the lowest near a shrimp farm. pH values during high tide and low tide ranged from 7.32 - 8.81 and 7.48 - 8.44, respectively with the station nearest to the coast showing the highest pH value during both tide levels. DO during high tide (4.80 - 8.08 mg/L) was higher than that during low tide (3.26 - 5.83 mg/L) in all stations. Lower DO values were observed during low tide than high tide and 80 % of DO readings were above 4.00 mg/L. TSS values were below 46 mg/L except for the station near to shrimp farm discharge. Chl-a was the highest at bottom water near a shrimp farm discharge station during low tide. BOD5 ranged from 0.38 - 3.29 mg/L and the highest occurred during low tide at surface water near the shrimp farm. Ninety five percent of the BOD5 and 95 % of TSS values complied with Class II of NWQS.